A bioinspired stiffness tunable sucker for passive adaptation and firm attachment to angular substrates - Goshtasbi, Arman; Sadeghi, Ali (Frontiers in Robotics and AI, 2023)
The ability to adapt and conform to angular and uneven surfaces improves the suction cup’s performance in grasping and manipulation. However, in most cases, the adaptation costs lack of required stiffness for manipulation after surface attachment; thus, the ideal scenario is to have compliance during adaptation and stiffness after attachment to the surface. Inspired by the capability of stiffness regulation in octopus suction cup, this article presents a suction cup that adapts to steep angular surfaces due to compliance and has high stiffness after attachment. In this design, the stiffness after attachment is provided by using granular jamming as vacuum driven stiffness modulation. Thus, the design is composed of a conventional active suction pad connected to a granular stalk, emulating a hinge behavior during adaptation and creating high stiffness by jamming granular particles driven by the same vacuum as the suction pad. During the experiment, the suction cup can adapt to angles up to 85° with a force lower than 0.5 N. We also investigated the effect of granular stalk’s length on the adaptation and how this design performs compared to passive adaptation without stiffness modulation.